Downton Abbey. Season 1 [videorecording (DVD)] - Smith, Maggie, 1934-2024; Bonneville, Hugh; Findlay, Jessica Brown, 1989-; McGovern, Elizabeth, 1961-; Carter, Jim, 1948-; Logan, Phyllis; Stevens, Dan, 1982-; Dockery, Michelle, 1981- (Masterpiece classic, 2011)
Set in an Edwardian country house in 1912, Downton Abbey portrays the lives of the Crawley family and the servants who work for them. In the drawing rooms, library, and beautiful bedrooms, with their tall windows looking across the park, lives the family, but below stairs are other residents, the servants, as fiercely possessive of their ranks as anyone above.